On-field low-frequency fatigue measurement after repeated drop jumps - Ridard, Jade; Rozand, Vianney; Millet, Guillaume Y.; Lapole, Thomas (Frontiers in Physiology, 2022)
Purpose: Monitoring fatigue is now commonly performed in athletes as it can directly impact performance and may further increase the risk of injury or overtraining syndrome. Among the exercise-induced peripheral alterations, low-frequency fatigue (LFF) assessment is commonly restricted to in-lab studies. Measuring LFF on-field would allow athletes and coaches to assess muscle fatigability on a regular basis. The aim of the present study was therefore to validate a new portable device allowing quadriceps LFF assessment in the field. Methods: LFF was assessed in 15 active and healthy participants before (PRE) and after (POST) a series of drop jumps. LFF was assessed thanks to a dedicated device recording evoked force to muscle submaximal electrical low- and high-frequency stimulation. Changes in the low- to high-frequency force ratio (further referred to as Powerdex® value) was compared to the changes in the ratio of evoked force induced by paired-pulses femoral nerve electrical stimulation at 10 and 100 Hz (i.e. DB10/DB100 ratio). Maximal voluntary contraction (MVC) and voluntary activation (VA) were also measured. Results: MVC decreased (p < 0.001) whereas VA was not affected by the fatiguing task (p = 0.14). There was a decrease in the DB10/DB100 ratio (from 96.4% to 67.3%, p < 0.001) as well as in the Powerdex value (from 74.0% to 55.7%, p < 0.001). There was no significant difference between POST values (expressed in percentage of PRE values) of DB10/DB100 ratio and Powerdex (p = 0.44) and there was a significant correlation between the changes in Powerdex® and DB10/DB100 (r = 0.82, p < 0.001). Conclusion: The on-field device we tested is a valid tool to assess LFF after a strenuous exercise consisting in repeated drop jumps as it evidences the presence of LFF similarly to a lab technique. Such a device can be used to monitor muscle fatigability related to excitation-contraction in athletes.